Stunting among children under 5 years of age in Surakarta City, Central Java - Indria Aulia Dewi; Siti Arifah (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2024)
Background: Stunting is defined as the growth of a child below the expected level for his or her age. It can occur during pregnancy, breastfeeding, and up to the first 1000 days (about 2 and a half years) of life. Stunting affects the brain development of the children, physical-motor growth, and has long-term implications for their future. The causes of stunting in children are multifaceted and can range from long-term inadequate nutrition to genetic and psychosocial factors.Purpose: To investigate demographics data of stunting among children under 5 years of age in Surakarta City, Central Java.Method: A quantitative design and descriptive analytical approach were used. The data were collected from a population of stunted children in the work area of the Pajang Community Health Centre between November and December of 2023. The research used purposive sampling and involved 93 respondents. Results: Finding characteristics of both children and mothers with specifically, 71% of the stunted children were categorized as short, 52.7% were male, and the majority had a normal birth length. Most mothers of stunted children are aged between 20 and 35 years, 50.5% of mothers are taller than 155 cm (about 5.09 ft), 52.5% of mothers have a high school education and 74.2% of mothers are unemployed. Conclusion: The characteristics of children and mothers about stunting are complex and interrelated. Therefore, health service providers should provide the best interventions with particular attention to both community and family-centered care.